Емкостные датчики для длинноволнового акустического контроля - Зайцева, Лилия Васильевна (Національний технічний університет "Харківський політехнічний інститут", 2018)
Рассматриваются с общих позиций состояние, перспективы и возможности применения емкостного метода неразрушающего контроля. Разработана математическая модель процесса возбуждения акустических волн (продольной и поверхностной) с помощью конденсатора, позволяющая проводить расчет выходного сигнала, для последующего выбора методов и средств приема данных акустических колебаний. Разработан макет устройства для реализации емкостного метода. Установлена возможность возбуждения и приема акустических колебаний емкостными преобразователями.

Consider from the common position present-day state, prospects and the possibility of non-destructive testing capacitive method using. Developed mathematical model of the process of acoustic wave’s excitation (longitudinal and surface) with a capacitor allow carrying out the output signal calculation for the subsequent choice of methods and devices for receiving the acoustic oscillations data. A device layout has been developed for realization of capacitive method. The possibility of excitation and reception of acoustic vibrations by capacitive transducers it has been established. As a result of the theoretical calculation of the propagation of acoustic waves, it is established that it is possible to receive such waves with a sufficiently high level of the electric signal in the low-frequency range of frequencies. In order to increase the level of the output signal of the capacitive converter, the geometrical parameters of the receiving and exciting capacitive converter are investigated.
Capacitive sensors for the long-wave acoustic control
Keywords: преобразователь; волна; transducer; wave